THE STATE OF ART IN VICTIMOLOGY IN THE REPUBLIC OF MACEDONIA - Gordana Lazetic; Aleksandra Gruevska Drakulevski (Iustinianus Primus Law Review, 2018)
The article provides a general picture on the state of art of victimology in the country, as well as short analyses of the victim-related data from official statistics on victimisation as well as data from victim surveys. Mostly the authors refer to the data and research findings on victimisation of several governmental and NGO key actors involved in victim protection. The authors present data on specific groups of victims. Also, the authors give a brief overview of cases with violation of victims’ rights, such as the Cases of the Special prosecution office (SJO), Kumanovo clashes in “Divo Naselje” and the Violent attack in the Macedonian Parliament (`Bloody Thursday`). The authors of the article conclude that victimology is a relatively neglected area of criminology in the country. The data are pretty scarce, so there is a need for improvements in terms of conducting surveys on victims, their rights, support and protection, etc.
Keywords: victimology, victimisation, victims, victim protection, victim surveys